Pengembangan Potensi Bakat Minat Siswa melalui Kegiatan Ekstrakurikuler di SD Istiqomah Bandung - Kinesti, Rakanita Dyah Ayu; Setyani, Yhayuk; Munawaroh, Ainatul; Saifulloh, Fayyadh; Falahuddin, Anim; Izzah, Faiqotul (Lembaga Yasin AlSys, 2022)
Development of potential talents and interests through extracurricular activities is important to do, potential talents and interests of students can develop if the environment is supportive. Through extracurricular activities, students can develop their potential talents and interests, and can also develop cognitive aspects, affective aspects and psychomotor aspects so that students are more active and independent. What characterizes a school is its extracurricular activities, because in providing activities it is adjusted to the school's vision and mission, so that each school has different types of extracurricular activities. In the development of extracurricular activities, it is also supported by policies from the Education unit, the availability of coaches, and also the availability of facilities in infrastructure from the Education unit. The purpose of this study was to obtain data on how to develop potential talents and interests through extracurricular activities at SD Istiqomah Bandung. In conducting this research using qualitative, namely through interviews, observation, and documentation. Based on the results of this study, the development of students' talents and interests through extracurricular activities at SD Istiqomah Bandung was considered and developed properly.